2018
DOI: 10.1186/s12937-018-0320-7
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of overweight/obesity in a Brazilian cohort after 13 years of follow-up

Abstract: BackgroundObesity is a chronic complex disease with an increasing prevalence around the world. Prospective studies in adult cohorts are needed to provide information about predictors of new-onset overweight/obesity on population-based levels. The aim of this study was to identify factors associated with the risk of an adult individual become overweight/obese after 13 years of follow-up.MethodsSecond phase of an observational population-based prospective cohort study in a small town in the Midwest region of Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…After the removal of duplicates, 2478 records were screened by title and abstract, of which 2397 were excluded, leaving 81 papers for full-text assessment. Fourteen studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] were found to meet eligibility criteria and were included in this review for quality appraisal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the removal of duplicates, 2478 records were screened by title and abstract, of which 2397 were excluded, leaving 81 papers for full-text assessment. Fourteen studies [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ] were found to meet eligibility criteria and were included in this review for quality appraisal.…”
Section: Resultsmentioning
confidence: 99%
“…However, only two of the included studies provided a specific explanation of strategies used to address incomplete follow-up [ 33 , 40 ]. Four studies did not adjust for energy intake, a key confounding factor to account for when exploring dietary predictors of weight gain [ 34 , 35 , 39 , 46 ]. Among the ten included studies, vegetable intake was measured using different validated food frequency questionnaires (FFQ) or short dietary questionnaires ( Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Small-for-gestational-age births affect approximately 1 in 10 newborns worldwide. Several studies have been performed to demonstrate that rapid postnatal weight gain early in life is related to obesity later [ 26 29 ]. However, we are not aware of any work suggesting optimal growth patterns in infancy for reducing the risk of SGA obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Predictors of overweight/obesity[ 22 ] and hypertension[ 21 ] were recently assessed using data from this same cohort. Differing from our study, neither one of these studies included mortality data as the main outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Sex, age, marital status (with or without partner) and income (monthly household income in units of minimum wage) were the sociodemographic characteristics assessed. Weight, height, body mass index (BMI) and waist circumference (WC) were obtained as described in detail previously [ 22 ].…”
Section: Methodsmentioning
confidence: 99%